(untitled) - McCarthy, Michael (Cambridge, UK, 2006)
Easy and enjoyable to teach, Touchstone is packed with new and exciting ideas, offering a fresh approach to the teaching and learning of English. Workbook 3 provides follow-up exercises for each two-page lesson in Student's Book 3, allowing for a thorough practice of new vocabulary, structures, and conversation strategies and providing extra reading and writing activities. A progress chart at the end of each unit helps students evaluate their progress and plan further study
Keywords: English language; Texbooks for foreign speakers,Problems, exercises, etc